PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE MEREK SAMSUNG PADA MAHASISWA UNIVERSITAS ALKHAIRAAT PALU - Susanti, Heni (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2017)
The purpose of this study to determine and analyze the influence of marketing mix on purchasing decisions of Samsung smartphone in Alkhairaat University?s students in Palu. Type of research is descriptive causal using purposive sampling technique, with a sample of 60 respondents. Method of analysis is multiple linear regressiosn by using computer program SPSS for Windows Release 16.0. The Hypothesis test show a significance level ?=0.05 and for the reliability test shows cronbach alpha coefficient values with the limit value coefficient of ?=0.60. The results of this study show that marketing mix significantly influences purchasing decisions with sig. value of 0,000. Partial test with standard ? = 0.05 shows the results of products (X1), price (X2), points (X3), and promotion (X4) significantly influence purchasing decisions with sig. value of 0,007, 0,000. 0.012, and 0.000, respectively. Alla variables have influence on purchasing decisions of 0.876 or 87.6%, while the remaining 12.4% is influenced by other variables.